2011
DOI: 10.5693/djo.01.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a visual aid on the comprehension of cataract surgery in a rural, indigent South Indian population

Abstract: Purpose-To determine whether a visual aid improves the understanding and retention of information presented during informed consent for rural, indigent patients presenting for cataract surgery.Materials and Methods-This was a randomized, unmasked, interventional study. We recruited patients who presented to the Hande Surgical Hospital in Chennai, India, for cataract surgery. Patients were randomized into two groups: verbal consent alone (group A) and verbal consent plus a poster (group B). Both groups complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Letters written by genetic counselors that included images had, on average, a lower reading level than those that did not include images. This finding is consistent with previous research (Delp and Jones 1996;Karan et al 2011) that found including images improves comprehension. Because images have been shown to have a correlation with increasing readability, it is concerning that 20 % of respondents had never thought about including images in patient letters and 14 % believed it would not be helpful.…”
Section: Readabilitysupporting
confidence: 94%
See 1 more Smart Citation
“…Letters written by genetic counselors that included images had, on average, a lower reading level than those that did not include images. This finding is consistent with previous research (Delp and Jones 1996;Karan et al 2011) that found including images improves comprehension. Because images have been shown to have a correlation with increasing readability, it is concerning that 20 % of respondents had never thought about including images in patient letters and 14 % believed it would not be helpful.…”
Section: Readabilitysupporting
confidence: 94%
“…Readability of patient letters can also be increased by including images. Images have been shown to increase comprehension (Delp and Jones 1996;Karan et al 2011). For example, Delp and Jones (1996) found that patients who were given medical information with visual aids were not only more likely to read the information, they were also more likely to understand the information.…”
Section: Introductionmentioning
confidence: 99%
“…Other reasons for exclusion included: incompatible study population (not cataract surgery patients) ( n = 4), no relevant study intervention (patient education about cataract surgery) ( n = 3), language of publication other than English ( n = 2), and no available full‐text ( n = 1). From reference lists of the located articles, we identified two additional RCTs eligible for systematic review, yielding 16 studies in this review …”
Section: Resultsmentioning
confidence: 99%
“…includes Austrian patients). Most studies employed multiple inclusion criteria, though six (38%) studies did not specify any inclusion criteria aside from the status of cataract surgery patient. In addition, only three (19%) studies reported the type of anesthesia employed during surgery (local anesthesia in two and topical anesthesia in one).…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of gene microarrays, Ahdesmäki et al 15 proposed use of robust M estimation of regression when dealing with biological time series models. Karan et al 16 assessed the use of visual aids when obtaining informed consent for cataract surgery, using linear regression model as their model of choice. The study of van Vliet et al 17 used robust linear regression to demonstrate that low plasma apolipoprotein E gene levels in midlife are associated with increased risk of Alzheimer's disease in later life.…”
Section: Introductionmentioning
confidence: 99%